Analysis of the Utilization of Online Product Registration Services ASROT BPOM by Traditional Medicines SME’s PPJAI Members Through the Technology Acceptance Model (TAM) Approach in the Working Area of the BPOM Banyumas - Winanto Winanto; Sri Widiyanesti (Eastasouth Institute, 2026)
This research will attempt to evaluate the degree of acceptance of the application of e-registration of traditional medicines and food supplements, otherwise known as the ASROT application, through the Indonesian Natural Herbal Medicine Association (PPJAI), with the application of the Technology Acceptance Model (TAM) approach, with the addition of the 'trust of the government' component. Digitalization of public services, such as traditional medicine registration, will increase the efficiency, transparency, and accountability of the services being rendered. However, with the adoption of the digital system, many challenges have arisen, such as adapting users to the system, the complexity involved, as well as its inability to provide users with the necessary features. This will explore the relationship of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Trust of the Government as seen in its impact on Attitude Towards Use (ATU), as well as its subsequent impact on Intention To Use (ITU) the application. With this, researchers will apply the use of a Quantitative method with a questionnaire as the medium through which the researchers will seek information from PPJAI members. This will allow the researcher the flexibility in terms of formulating their hypotheses that will seek to show its effect on its enjoyable use, with the addition that the ease with which the application will allow the user, as well as its reliance on the trust that the citizen gives. This will offer strategic recommendations with regard to this aspect, as researchers will seek to evaluate them. With this, researchers will offer theoretical contributions with regard to the literature being established as it relates to this aspect.